Freedom of Choice and Uniqueness of Morality - Nikolajčevas, B. (Problemos, 1979)
The author of the present paper is guided by the assumption that the concept of the freedom of choice in Soviet publications is either limited to a possibility of choice, or treated as independent of this possibility which is objectively conditioned. Therefore the author finds it relevant to point out that the possibility of choice happens to be merely a prerequisite of the freedom of choice as an essential condition of its realization. The uniqueness of morality lies in the fact that the choice of a certain mode of behaviour has to be conscious and unregulated. The paper also deals with the process of moral development of the personality in ontogenesis. It is stated in conclusion that subjective freedom may come to be realized as genuine only in reciprocal relation with man's activity which rests on the rightly comprehended necessity.